Development of Democracy and Political Challenges in the Digital Era - Ramdan, Muhammad (International Journal of Education, Information Technology, and Others, 2024)
Democracy faces various new challenges in the digital era, which is shaped by rapid changes in information and communication technology. This research explores the impact of digital technology on democracy, especially through the phenomena of social media and disinformation. On the one hand, digital technology offers greater possibilities for political participation and citizen empowerment. Social media, for example, has become a powerful tool for political mobility and social activism, allowing individuals to express opinions, mobilize support, and even influence public policy. On the other hand, the digital era also brings challenges such as the spread of fake news and disinformation which can damage the foundations of public trust in democratic institutions. Additionally, the use of personal data by large platforms in politics, as seen in the Cambridge Analytica scandal, raises serious questions about privacy and political manipulation. This study examines various strategies used by states and non-governmental organizations to address this problem, including social media regulation, media education, and digital literacy campaigns. This research uses qualitative analysis of data obtained through interviews, surveys and relevant secondary sources. The findings show that although digital technologies promise to increase democratic participation, strict oversight and accountability of all stakeholders is necessary to protect the integrity of the democratic process. This research provides insight into how democracies can adapt and survive in the face of the challenges presented by the digital era